Areas of recent developments for shape memory alloy: A review. (2022) - Singh Rajput, Gautam; Vora, Jay; Prajapati, Parth; Chaudhari, Rakesh
Abstract: Shape memory alloys (SMA) also known as smart materials, can return to their original shape when being heated. These materials memorize their original form and return to their original form when heated. During the past few years, it has drawn tremendous interest in a wide range of applications. It is attracting researchers to explore various unexplored horizons and implementing the material to take advantage of it, due to their unique properties of regaining their original shape. The development of 3-D printing has revolutionized the manufacturing field and the possibility of making SME with additive manufacturing has been reviewed. This review highlights the general concept of SMA, history, shape memory effect (SME), various types of SMA, recent developments in the fabrication technique of SMA, and its application have been discussed in detail. The latest application of SMA in the field of automotive, aerospace, marine, robotics, structures, and biomedical has been reviewed while discussing its challenges and advantages.